Effect of Addition of Dexamethasone to Local Anaesthetics in Supraclavicular Brachial Plexus Block (Journal of Armed Forces Medical College, Bangladesh, 2011)
Introduction: Many-a-time local anaesthesia appears as a very effective alternative of general one. Different additives have been used to prolong regional blockade. Objective: This prospective study designed to evaluate the effect of dexamethasone added to local anaesthetics on the onset and duration of supraclavicular brachial plexus block. Methods: Sixty adult patients undergoing various orthopaedic surgeries on forearm and around the elbow under supraclavicular brachial plexus block were selected and divided into 2 groups of 30 each. In group-A patients received 35 ml of mixture of lignocaine 2%, bupivacaine 0.5% while in group-B patients received the same amount of local anaesthetics with dexamethasone (8 mg). The onset of sensory and motor block and duration of analgesia in two groups were compared and development of complications were observed. Result: The two groups were comparable in demographic data. The mean onset time of sensory block was 11.64±2.19 minutes in group A and 9.89±1.97 minutes in group B and difference was statistically significant (p